Empowering Women: Uncovering Financial Inclusion Barriers - Maheswari, Mrs.M.; Vivek, Bala Reva (Advances in Social Sciences Research Journal, 2016)
In recent years, developing countries including India have witnessed significant efforts by civil society organisations and governments to promote thrift activities among the poor especially women. This has been followed by interventions in the area of micro-credit and microfinance. The designation of 2005 as the International Year of Micro credit by the United Nations helped to raise global awareness on the pivotal role that more inclusive finance can play in achieving the Millennium Development Goals. Globally, the focus is now on financial inclusion and on strategies to make available a range of financial products and services that meet the specific needs of the poor. This article is an attempt to ascertain the awareness of Financial Inclusion among rural women in Tirunelveli District.